Homogeneous Glacial Landscapes Can Have High Local Variability of Strontium Isotope Signatures: Implications for Prehistoric Migration Studies - Thomsen, Erik; Andreasen, Rasmus; Rasmussen, Tine L. (Frontiers in Ecology and Evolution, 2021)
Increasingly, strontium (Sr) isotopes are used to distinguish locals and migrants in prehistoric studies, by measuring 87Sr/86Sr in human remains and comparing these values to the distribution of the bioavailable 87Sr/86Sr in the study area, often in surface water. However, it has recently been shown that agricultural lime can have a substantial impact on the 87Sr/86Sr ratio and strontium concentration in surface water in areas where soils are low- to non-calcareous. Agricultural lime is rich in strontium with low 87Sr/86Sr ratios, such that interpretations of prehistoric migration based on surface waters affected by agricultural lime often overestimate the number of migrants in a given area. However, the impact of agricultural lime was questioned in a new study, which argues that strontium derived from agricultural lime is retained in the topsoil of the fields and therefore do not contaminate the surface water. In the present study and in a companion study in this volume, we show that strontium derived from agricultural lime is highly mobile in soils, and so contaminate surface waters extensively. We also show that the 87Sr/86Sr ratios are consistently higher in waters from “pristine areas” (where no agricultural lime has been applied within a distance of 150 m from the sample locality) than in water from farmland, thus confirming that it is of vital importance for accurate mapping of isoscapes to avoid sampling waters contaminated by agricultural lime. Our new measurements of 87Sr/86Sr ratios in central Jutland, Denmark, raise the highest measured values to 0.7186. High values between 0.7140 and 0.7156 occur repeatedly and it is apparent that nearly all prehistoric human finds in Jutland, previously believed to have journeyed from afar are more likely of local origin. Furthermore, we show that carbonate-rich areas along the coast of southwest Zealand carry high 87Sr/86Sr values (0.7112–0.7132), where we would expect low values. This surprising result indicates that nearly all humans buried at the Viking Age site, Trelleborg could well have originated locally, in contrast to past studies, which have suggested that about 50% of the burials were of individuals who came from afar.